Cross-cultural patterns in mobile playtime: an analysis of 118 billion hours of human data - Zendle, D; Flick, C; Halgarth, D; Ballou, NB; Demediuk, S; Drachen, A (Springer Nature, 2023)
Despite the prevalence of gaming as a human activity, the literature on playtime is uninformed by large-scale, high-quality data. This has led to an evidence-base in which the existence of specific cultural gaming cultures (e.g. exceptional levels of gaming in East Asian nations) are not well-supported by evidence. Here we address this evidence gap by conducting the world’s first large-scale investigation of cross-cultural differences in mobile gaming via telemetry analysis. Our data cover 118 billion hours of playtime occurring in 214 countries and regions between October 2020 and October 2021. A cluster analysis establishes a data-driven set of cross-cultural groupings that describe differences in how the world plays mobile games. Despite contemporary arguments regarding Asian exceptionalism in terms of playtime, analysis shows that many East Asian countries (e.g., China) were not highly differentiated from most high-GDP Northern European nations across several measures of play. Instead, a range of previously unstudied and highly differentiated cross-cultural clusters emerged from the data and are presented here, showcasing the diversity of global gaming.